EFEKTIVISTAS MEDIA VIDIO TUTORIAL DALAM MENINGKATKAN KETERAMPILAN LIFE SKILL MEMBUAT SELAI DARI ALOE VERA BAGI ANAK TUNARUNGU DI SLB PERWARI PADANG (Pre Exsperimental Design kelas B di SLB Perwari Padang) - Fauziyyah, Putry; Armaini, Armaini (Universitas Islam Negeri Alauddin Makassar, 2021)
This study discusses the effectiveness of video tutorial media in improving the life skills of making aloe vera jam for deaf children. The subjects of this study were five deaf children. This study used a pre-experimental design method, the abilities assessed by the pretest and posttest designs were processed and compared using the Wilcoxon Sign Rank Test.Based on the results of the pretest and posttest, it is known that the pretest average value is 24.60 and the posttest average value is 84. The average value is then processed to find the difference using the Wilcoxon Sign Rank Test. From the results of data analysis obtained Zhitung = -2.032 with probability or Asymp Sig (2-tailed) = 0.42 at a significant level of 5% and α = 0.05. The alternative hypothesis is accepted because Zhitung> Asymp. Sig. (2-tailed). So it can be concluded that the video tutorial media is effective in improving the life skills of making aloe vera jam for deaf children at SLB Perwari, Padang.Key words: Life skills, making aloe vera, deaf